Mg2+‐mediated autophagy‐dependent polarization of macrophages mediates the osteogenesis of bone marrow stromal stem cells by interfering with macrophage‐derived exosomes containing miR‐381. Issue 7 (2nd November 2021) - Zhu, Yong; Zhao, Shushan; Cheng, Liang; Lin, Zhangyuan; Zeng, Min; Ruan, Zhe; Sun, Buhua; Luo, Zhongwei; Tang, Yifu; Long, Haitao
Abstract: Magnesium ion (Mg 2+ ) has received increased attention due to the roles it plays in promoting osteogenesis and preventing inflammation. This study was designed to investigate the mechanism by which Mg 2+ influences the osteoblastic differentiation of bone marrow stromal stem cells (BMSCs). The polarization of Mø (macrophages) was measured after treatment with Mg 2+ . Meanwhile, autophagy in Mø was measured by detecting LC3B expression. Mø‐derived exosomes were isolated and cocultured with BMSCs; after which, osteogenic differentiation was evaluated by Alizarin Red staining and detection of alkaline phosphatase (ALP). Our results showed that Mg 2+ could induce autophagy in macrophages and modulate the M1/M2 polarization of macrophages. Mg 2+ ‐mediated macrophages could facilitate the osteogenic differentiation of BMSCs by regulating autophagy, and this facilitation by Mg 2+ ‐mediated macrophages was closely related to macrophage‐derived exosomes, and especially exosomes containing miR‐381. However, miR‐381 in macrophages did not influence autophagy or the polarization of Mg 2+ ‐mediated macrophages. Furthermore, macrophage‐derived exosomes containing miR‐381 mainly determined the osteogenic differentiation of BMSCs. Mg 2+ ‐mediated macrophages were shown to promote the osteogenic differentiation of BMSCs via autophagy through reducing miR‐381 in macrophage‐derived exosomes. In conclusion, our results suggest Mg 2+ ‐mediated macrophage‐derived exosomes containing miR‐381 as novel vehicles for promoting the osteogenic differentiation of BMSCs.